THE INFLUENCE OF HEALTH EDUCATION ON STUNTING PREVENTION TO NUTRITION KNOWLEDGE OF PREGNANT WOMEN IN PUSKESMAS GODONG I - Erna Marliana; Wahyu Dewi Hapsari; Dewi Sapta Wati (Jurnal Profesi Bidan Indonesia, 2024)
Background: Stunting is a national problem that needs serious attention by many parties. Various methods and approaches have been implemented to prevent stunting. Health education about nutrition for pregnant women is expected to be able to prevent stunting, especially in Grobogan Regency. Purpose: To determine the effect of health education on the nutritional knowledge of pregnant women at the Godong I Health Center. Method: The type of research were quantitative with a correlational design. The approach that used is cross sectional study. The sample of this study were pregnant women on Puskesmas Godong I with a total sampling was 175 respondents. The data collection is used a questionnaire. Data were analyzed by bivariate analyzed using Wilcoxon Test. Results: Majority of responden were enough knowledge (pre education) is about 78 (44,6%) of responden and good knowledge (Post education) is 146 (83,5%) of respondents. Bivariate   analyzed is showing p-value 0,000. Conclusion: they were influence of health education on stunting prevention to nutrition knowledge of pregnant women In Puskesmas Godong I.